Phase II study of nab-paclitaxel in refractory small bowel adenocarcinoma and CpG island methylator phenotype (CIMP)-high colorectal cancer. (23rd October 2017) - Overman, M J; Adam, L; Raghav, K; Wang, J; Kee, B; Fogelman, D; Eng, C; Vilar, E; Shroff, R; Dasari, A; Wolff, R; Morris, J; et al.
Abstract: Background: Hypermethylation of promoter CpG islands [CpG island methylator phenotype (CIMP)] represents a unique pathway for the development of colorectal cancer (CRC), characterized by lack of chromosomal instability and a low rate of adenomatous polyposis coli ( APC ) mutations, which have both been correlated with taxane resistance. Similarly, small bowel adenocarcinoma (SBA), a rare tumor, also has a low rate of APC mutations. This phase II study evaluated taxane sensitivity in SBA and CIMP-high CRC. Patients and methods: The primary objective was Response Evaluation Criteria in Solid Tumors version 1.1 response rate. Eligibility included Eastern Cooperative Oncology Group performance status 0/1, refractory disease, and SBA or CIMP-high metastatic CRC. Nab-paclitaxel was initially administered at a dose of 260 mg/m 2 every 3 weeks but was reduced to 220 mg/m 2 owing to toxicity. Results: A total of 21 patients with CIMP-high CRC and 13 with SBA were enrolled from November 2012 to October 2014. The efficacy-assessable population (patients who received at least three doses of the treatment) comprised 15 CIMP-high CRC patients and 10 SBA patients. Common grade 3 or 4 toxicities were fatigue (12%), neutropenia (9%), febrile neutropenia (9%), dehydration (6%), and thrombocytopenia (6%). No responses were seen in the CIMP-high CRC cohort and two partial responses were seen in the SBA cohort. Median progression-free survival was significantly greater in the SBA cohort than in the CIMP-high CRC cohort (3.2 months compared with 2.1 months, P = 0.03). Neither APC mutation status nor CHFR methylation status correlated with efficacy in the CIMP-high CRC cohort. In vivo testing of paclitaxel in an SBA patient-derived xenograft validated the activity of taxanes in this disease type. Conclusion: Although preclinical studies suggested taxane sensitivity was associated with chromosomal stability and wild-type APC, we found that nab-paclitaxel was inactive in CIMP-high metastatic CRC. Nab-paclitaxel may represent a novel therapeutic option for SBA.